Communities at the nexus of entrepreneurship and societal impact: A cross-disciplinary literature review - Bacq, Sophie; Hertel, Christina; Lumpkin, G.T. (Journal of business venturing, 2022)
Although there is wide recognition of the importance of entrepreneurship for generating societal impact, entrepreneurial activities alone rarely achieve a positive impact without the engagement of communities. To date, however, entrepreneurship researchers have tended to overlook the importance of community for creating societal impact through entrepreneurship, and lack a comprehensive understanding of the nature and roles of communities. To address this, we conduct a systematic review of the literature published in 51 journals across the Management and Entrepreneurship, Economic Development/Community Development, Economic Geography and Regional Science, Energy, and Public Administration disciplines that makes three contributions. First, it identifies a new typology of community and proposes a comprehensive framework of roles through which societal impact is created by entrepreneurship for, in, with, enabled by, and driven by communities. Second, it demonstrates that the key to understanding how community relates to societal impact creation is to jointly account for both its type(s) and role(s). By linking community types and roles, the findings also suggest a theoretical contribution based on the relationship between the degree of formalization of a community type, and the degree of agency that a community role enacts. Third, the review underscores that communities are not just static settings but can also be dynamic actors in efforts to use entrepreneurship to create societal impact. Our cross-disciplinary review highlights trends and gaps in the extant literature and provides researchers with an evidence-based research agenda to guide future inquiry on this vital topic. •Community research lacks construct clarity and an integrative framework across disciplines.•We review 227 articles across five major disciplines on entrepreneurship, community, and societal impact.•We find five community types—place, identity, fate, interest, practice.•We find six community roles—beneficiary, context, supporter, partner, opportunity creator, entrepreneur.•Communities are often dynamic—morphing and emerging anew—in pursuit of entrepreneurship and societal impact creation.